2016
DOI: 10.1084/jem.20141388
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal eosinophils regulate Th17 cells by producing IL-1 receptor antagonist

Abstract: Eosinophils play proinflammatory roles in helminth infections and allergic diseases. Under steady-state conditions, eosinophils are abundantly found in the small intestinal lamina propria, but their physiological function is largely unexplored. In this study, we found that small intestinal eosinophils down-regulate Th17 cells. Th17 cells in the small intestine were markedly increased in the ΔdblGATA-1 mice lacking eosinophils, and an inverse correlation was observed between the number of eosinophils and that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 51 publications
6
85
0
1
Order By: Relevance
“…Although eosinophils are most known as proinflammatory cells that contribute to the pathogenesis of various allergic diseases, more recent studies reveal remarkable functional diversity of eosinophils in different tissues (77). For example, unlike eosinophils from the lung or blood, small intestinal eosinophils display extended lifespans (75, 76). Sugawara et al recently reported that small intestinal eosinophils constitutively secrete high levels of IL-1 receptor antagonist (IL-1Ra), a natural inhibitor of IL-1β, which is promoted by production of GM-CSF by intestinal epithelial cells in a gut microbiota-independent manner.…”
Section: Regulation Of Myeloid Cells By the Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Although eosinophils are most known as proinflammatory cells that contribute to the pathogenesis of various allergic diseases, more recent studies reveal remarkable functional diversity of eosinophils in different tissues (77). For example, unlike eosinophils from the lung or blood, small intestinal eosinophils display extended lifespans (75, 76). Sugawara et al recently reported that small intestinal eosinophils constitutively secrete high levels of IL-1 receptor antagonist (IL-1Ra), a natural inhibitor of IL-1β, which is promoted by production of GM-CSF by intestinal epithelial cells in a gut microbiota-independent manner.…”
Section: Regulation Of Myeloid Cells By the Gut Microbiotamentioning
confidence: 99%
“…Sugawara et al recently reported that small intestinal eosinophils constitutively secrete high levels of IL-1 receptor antagonist (IL-1Ra), a natural inhibitor of IL-1β, which is promoted by production of GM-CSF by intestinal epithelial cells in a gut microbiota-independent manner. By suppressing the levels of IL-1β in the small intestine, eosinophils suppress Th17 cells, thereby playing a critical role in the maintenance of intestinal homeostasis (76). The function of this major leukocyte population in the gut, however, has not been extensively explored, either in the steady state or in the context of food allergies.…”
Section: Regulation Of Myeloid Cells By the Gut Microbiotamentioning
confidence: 99%
“…81). GM-CSF is constitutively secreted by intestinal epithelial cells 82 and probably maintains intestinal eosinophils in a unique activation state 83 , such that it may be particularly important to the homeostatic functions of intestinal tissue eosinophils. In vivo , the tissue accumulation of eosinophils is ultimately determined by a complex balance between signalling induced by pro-survival factors such as IL-3, IL-5 and GM-CSF and signalling through eosinophil surface-expressed inhibitory receptors (reviewed in REF.…”
Section: Regulating Tissue Eosinophilsmentioning
confidence: 99%
“…Indeed, both IL-5 and eosinophildeficient mice harbor increased numbers of N. brasiliensis larvae after secondary infection, 89 with similar results during secondary T. spiralis infection. 200 Furthermore, eosinophils negatively regulate Th17 cells 201 and promote the expansion of regulatory T cells in the steady state 198,202 that might affect overall inflammation, illustrating their complex contribution to tissue homeostasis. Similarly, whereas resident intestinal macrophages are mostly suppressive in nature and do not act inflammatory to pathogen stimulation, type 2 cytokines give rise to alternatively activated macrophages that might contribute to the expulsion of certain parasites.…”
Section: Resolutionmentioning
confidence: 99%